2013
DOI: 10.3310/hta17290
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the clinical effectiveness and cost-effectiveness, and economic evaluation, of denosumab for the treatment of bone metastases from solid tumours

Abstract: Denosumab offers an alternative, or additional, treatment for the prevention of skeletal-related events (SREs) in patients with bone metastases from solid tumours

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 248 publications
1
60
0
1
Order By: Relevance
“…Therefore, great care was taken in the selection of inputs and assumptions for this model so as to provide a defensible estimate of denosumab's ICUR relative to zoledronic acid. For example, we adopted assumptions that favored denosumab, such as the assumption that all SREs would be sufficiently severe so as to result in substantial additional healthcare costs, even though Hillner et al 27 and other reports 15 have suggested that some SREs may be asymptomatic or have limited or no impact on costs and QALYs. It should also be noted that the protocol of the Fizazi et al 5 clinical trial upon which this analysis is based required that skeletal events be assessed by skeletal surveys every 12 weeks or by radiographic assessments during the course of care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, great care was taken in the selection of inputs and assumptions for this model so as to provide a defensible estimate of denosumab's ICUR relative to zoledronic acid. For example, we adopted assumptions that favored denosumab, such as the assumption that all SREs would be sufficiently severe so as to result in substantial additional healthcare costs, even though Hillner et al 27 and other reports 15 have suggested that some SREs may be asymptomatic or have limited or no impact on costs and QALYs. It should also be noted that the protocol of the Fizazi et al 5 clinical trial upon which this analysis is based required that skeletal events be assessed by skeletal surveys every 12 weeks or by radiographic assessments during the course of care.…”
Section: Discussionmentioning
confidence: 99%
“…Since it is likely that spinal cord compression and surgery to the bone would be associated with worse decrease in utility than fractures or radiation to the bone, it was assumed that the disutility for both surgery to the bone and spinal cord compression would be À0.17 (the lowest end of the confidence interval reported by Weinfurt et al). The use of SRE-related utilities reported 15 . SRE-related disutility was permanently maintained following an SRE.…”
Section: Sre Inputsmentioning
confidence: 97%
“…Nonetheless, treatment decisions may not solely depend on the efficacy profile of a drug therapy; factors such as the safety profile (e.g., adverse events), mode of drug administration (e.g., intravenous vs. subcutaneous route), and out-of-pocket costs to patients may also play an important role. In addition to the superior efficacy of denosumab over zoledronic acid, the attributes that may influence decisions are different between the two options [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…A very recent systematic review of the clinical effectiveness and cost-effectiveness of denosumab for the treatment of bone metastases compared denosumab with zoledronic acid and placebo [20]. The study demonstrated that denosumab was effective in delaying SREs, but it was similar with regard to quality of life and pain.…”
Section: Denosumab Versus Zoledronic Acid In Crpcmentioning
confidence: 94%